2014
DOI: 10.1371/journal.pone.0098977
|View full text |Cite
|
Sign up to set email alerts
|

Does Competition Really Bring Out the Worst? Testosterone, Social Distance and Inter-Male Competition Shape Parochial Altruism in Human Males

Abstract: Parochial altruism, defined as increased ingroup favoritism and heightened outgroup hostility, is a widespread feature of human societies that affects altruistic cooperation and punishment behavior, particularly in intergroup conflicts. Humans tend to protect fellow group members and fight against outsiders, even at substantial costs for themselves. Testosterone modulates responses to competition and social threat, but its exact role in the context of parochial altruism remains controversial. Here, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
98
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(118 citation statements)
references
References 59 publications
19
98
1
Order By: Relevance
“…in conjunction with high cortisol) testosterone might be associated with enhanced empathy is congruent with recent evidence showing that high exogenous and endogenous androgens may sometimes promote altruistic behavior (van Honk et al 2012;Diekhof et al 2014). For example, Diekhof and colleagues reported that in the context of between-group competition, high testosterone men not only favored outgroup hostility but also promoted ingroup prosocial behavior (Diekhof et al 2014).…”
Section: Discussionsupporting
confidence: 69%
“…in conjunction with high cortisol) testosterone might be associated with enhanced empathy is congruent with recent evidence showing that high exogenous and endogenous androgens may sometimes promote altruistic behavior (van Honk et al 2012;Diekhof et al 2014). For example, Diekhof and colleagues reported that in the context of between-group competition, high testosterone men not only favored outgroup hostility but also promoted ingroup prosocial behavior (Diekhof et al 2014).…”
Section: Discussionsupporting
confidence: 69%
“…Recent human data suggest that testosterone might simultaneously promote in-group bonds while increasing between-group hostility (Diekhof et al 2014). Species exhibiting cooperative territorial behavior should provide opportunities for investigating this dynamic.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Furthermore, testosterone promotes masculinization and correlates negatively with prosocial behaviors that are important for childrearing (e.g., nurturance and empathy) and maternal attributes [3,9,12] (but also see [16,17] for a different role of testosterone in male-male cooperation during intergroup conflict). During parenthood testosterone levels decrease, which could be an adaptation to facilitate parental investment [18,19].…”
Section: Introductionmentioning
confidence: 99%